Asymmetric Synthesis of Amines through Rhodium-Catalyzed C–H Amination with Sulfonimidoylnitrenes - Darses, Benjamin; Jarvis, Amanda G.; Mafroud, Abdel-Kader; Estenne-Bouhtou, Geneviève; Dargazanli, Gihad; Dauban, Philippe (Synthesis, 2013)
An efficient asymmetric C–H amination of benzylic and allylic substrates, as well as of adamantane derivatives, through catalytic C–H insertion of a chiral nitrene is reported. The reaction involves a chiral rhodium(II) complex, an iodine(III) oxidant, and a sulfonimidamide as a nitrene precursor. Experimental protocols for the preparation of the reagents and the catalytic nitrene are provided. The C–H amination can provide the corresponding amino derivatives on a gram scale. Various methods for the cleavage of the sulfonimidoyl group to give the corresponding tert-butoxycarbonyl- or acetyl-protected optically pure amines are also described.
Keywords: rhodium; amines; nitrene; asymmetric catalysis; C–H amination